Closure - Journal of Infrastructure & Facility Asset Management (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
Scope of JIFAM PaperJIFAM accepts papers on Infrastructure & Facility Asset Management. The scope of the topic includes, but not limited to the following.- I & F Function- I & F Demand - Supply- I & F User Behavior- I & F Evaluation- I & F Policy- I & F Preliminary Idea- I & F Planning- I & F Design- I & F Construction- I & F Administration Aspects- I & F Technical Certification- I & F Information System- I & F Operation System- I & F Maintenance System- I & F Disposal- I & F Economics & Financial Aspect- I & F Spatial & Environmental Aspect- I & F Sustainability Aspects- I & F Strategic Aspect- Decision Making for I&FAM- Statistics for I&FAM- Mathematics for I&FAM- Operation Research for I&FAM- I & F Managing Organisation Aspect